Occupational exposure for asbestos-related disease groups: geomapping of the last 5 years in Italy. (30th September 2020) - Vinci, A; Ingravalle, F; D'Ercole, M; Mancinelli, S; Lucaroni, F; Palombi, L
Abstract: Background: Asbestos-related diseases are a public health challenge in Italy: the country has been a major producer and user of asbestos since World War II until complete ban in 1992. Several contaminated sites and structures across the country have never been decontaminated: incidence peak of asbestos-related diseases is expected somewhen between 2015 and 2020. Study objective is to investigate incidence of asbestos-related diseases in Italy in the last 5 years, from both a chronological and geographical perspective. Methods: Ascertained diagnoses of asbestos-related diseases among workers were collected from the INAIL public registry from 2014 to 2018. Yearly incidence rate was estimated per province (incident cases per million workers) and mapped by year. Global incidence quota by working sector and sub-sector was also calculated. Results: 8.620 cases have been reported. Incidence rate rapidly increased from 2014, peaking at 7, 2 new cases per 100.000 workers in 2015. Afterwards, the number of ascertained cases decreased. There is a clear gradient distribution between northern and southern Italian provinces, with the highest rates in Northern Italy (especially in year 2014) and declining over time. Mesothelioma (all variants) was the most common disease, (2.995 cases, 35% of total), followed by pleural plaques (2.955 cases, 34%), pneumoconiosis (1.327 cases, 15%) and cancer of lungs/respiratory tract (1.298 cases, 14%). Most affected category was that of metal workers, but construction, transportation and electricity workers were also affected. Conclusions: Detailed surveillance with mapping support is an effective tool for public health servants to locally manage prevention programs targeted on occupational risk. This is especially true for areas with active industries in the most affected sectors. Key messages: Asbestos does not mean mesothelioma, but also other diseases that impact on workforce health status. Pneumoconiosis and other oral and respiratory cancers are also associated with asbestos exposure. Risk management should be tailored for a wider array of worker types than usually considered, since such exposure happens in sectors that are not traditionally related to asbestos exposure.